Expansion of Primary Human AML by Aryl Hydrocarbon Receptor Antagonism Minimally Affects Leukemic Transcriptional Profiles but Alters Cellular Metabolism - Casado, Fanny L.; Salci, Kyle R.; Shapovalova, Zoya; Guezguez, Borhane; Collins, Tony J.; Bhatia, Mickie (Journal of Hematology Research, 2015)
Small molecule-based antagonism of the aryl hydrocarbon receptor (AHR) by StemRegenin1 (SR1) promotes ex vivo expansion and maintenance of primary human hematopoietic stem cells (HSCs) as well as acute myeloid leukemia (AML) cells. However, basis and nature of SR1 induced expansion of human AML remains unknown. Here, global expression profiling on 7 clinically diverse human AML patient samples treated ex vivo with a synthesized analog of SR1 (aSR1) uncovered that only as few as 750 genes were differentially regulated. Uniquely, aSR1 treatment did not modulate self-renewal associated pathways including Hedgehog, Notch or Wnt across patient samples, but instead resulted in overall upregulation of the oxidative phosphorylation metabolic pathway. Higher oxygen consumption rates, along with increased sensitivity to the chemotherapeutic agent cytarabine (AraC) validated that aSR1-induced transcriptional profiles lead to functional enhancement of oxidative phosphorylation. Our study reveals that aSR1 induces minor alterations to the leukemic transcriptional profile leading to a shift in cellular metabolism. This finding should further instruct use of SR1-mediated expansion for mechanistic studies of leukemic self-renewal and the development of drug screening platforms using patient specific AML samples.